Synthesis and x-ray investigation of novel nanostructured copper-zinc manganites of lanthanum and alkali metals - Kasenov, B.K.; Kasenova, Sh.B.; Sagintaeva, Zh.I.; Nukhuly, A.; Turtubaeva, M.O.; Bekturganov, Zh.S.; Zeinidenov, A.K.; Kuanyshbekov, E.E.; Issabaeva, M.A. (KU publ., 2021)
The aim of this work is to synthesize new nanostructured copper-zinc lanthanum and alkaline metal manganites. Polycrystalline copper-zinc manganites of lanthanum and alkali metals were synthesized by the method of ceramic technology from lanthanum (III), copper (II), zinc (II), manganese (III) oxides, and lithium, sodium, and potassium carbonates in the range of 800-1200 oC. Nanostructured particles were obtained by grinding the synthesized polycrystalline compounds at the «MM301» vibration mill of «Retsch» (Germany). By indexing X-ray images of nanostructured copper-zinc lanthanum and alkaline metal manganites, it was found that they crystallize in cubic syngony. Their lattice parameters are determined. There is a pattern in the change of the lattice parameters from the ionic radii of alkaline metals.
Құрамында сілті металдары бар жаңа наноқұрылымды мыс-мырыш манганиттерін синтезі мен рентгенографиялық тұрғыдан зерттеу.
Cинтез и рентгенографическое исследование новых наноструктурированных медно-цинковых манганитов содержащих щелочные металлы.
Keywords: copper-zinc manganite; lanthanum; alkali metals; synthesis; nanostructured particles of X-ray phase analysis